THE ROLE OF EMPLOYEE ENGAGEMENT IN ENHANCING ORGANIZATIONAL PERFORMANCE - Siswandri; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Employee engagement has become a critical determinant of organizational performance in today’s competitive business environment. This article explores the multidimensional nature of employee engagement, encompassing emotional, cognitive, and behavioral components, and examines the factors that influence it, such as leadership practices, organizational culture, recognition systems, and career development opportunities. Engaged employees demonstrate higher levels of productivity, innovation, and loyalty, which directly contribute to improved organizational outcomes. By analyzing both theoretical perspectives and practical strategies, this study highlights how transparent communication, participative decision-making, reward systems, and growth opportunities can enhance engagement. The article also emphasizes the importance of aligning employee goals with organizational objectives, fostering a supportive work environment, and recognizing achievements to sustain motivation. Findings suggest that organizations that prioritize employee engagement not only improve individual performance but also create resilient, high-performing teams capable of achieving long-term strategic success.